2005
DOI: 10.1007/s11055-005-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Evoked brain potentials in adolescents in normal conditions and in attention deficit during solution of tasks requiring recognition of short-duration acoustic stimuli

Abstract: This study compares the effectiveness of the frequency-based recognition of short acoustic stimuli in groups of adolescents with attention deficit and normal measures of attention in conditions of the standard "oddball" paradigm. Stimuli of duration 50 msec yielded insignificant intergroup differences, though adolescents with attention deficit discriminated signal of duration 11 msec significantly worse. These showed significant differences in evoked brain potentials even with standard stimuli, with a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In our task, we found that adolescent FRNs were more negative than adult FRNs in every condition. This parallels a commonly reported phenomenon in developmental studies using the oddball paradigm to elicit an N200 (Aleksandrov, Polyakova, & Stankevich, ; Enoki, Sanada, Yoshinaga, Oka, & Ohtahara, ; Friedman, Brown, Vaughan, Cornblatt, & Erlenmeyer‐Kimling, ; Johnstone, Barry, Anderson, & Coyle, ; Mueller, Brehmer, von Oertzen, Li, & Lindenberger, ). In these studies, not only was the N200 to the infrequently presented target stimuli larger in children than in adults, but frequently presented standard stimuli also elicited an N200 in children and adolescents, but not in adults.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our task, we found that adolescent FRNs were more negative than adult FRNs in every condition. This parallels a commonly reported phenomenon in developmental studies using the oddball paradigm to elicit an N200 (Aleksandrov, Polyakova, & Stankevich, ; Enoki, Sanada, Yoshinaga, Oka, & Ohtahara, ; Friedman, Brown, Vaughan, Cornblatt, & Erlenmeyer‐Kimling, ; Johnstone, Barry, Anderson, & Coyle, ; Mueller, Brehmer, von Oertzen, Li, & Lindenberger, ). In these studies, not only was the N200 to the infrequently presented target stimuli larger in children than in adults, but frequently presented standard stimuli also elicited an N200 in children and adolescents, but not in adults.…”
Section: Discussionsupporting
confidence: 83%
“…These data are of particular relevance to our study as it has recently been proposed that the ERN, FRN, and the N200 reflect the same physiological phenomenon; they are all negative waves generated in the ACC that are elicited by unexpected task‐relevant stimuli or conflict, and that the modulation of FRN amplitude is driven primarily by neural activity elicited by positive, correct, or rewarding feedback (Baker & Holroyd, ; Holroyd, Pakzad‐Vaezi, & Krigolson, ). If this is true, then the finding that the FRN is larger in children and adolescents is not surprising, given that the N200 has also been shown to decrease with age (Aleksandrov et al., ; Enoki et al., ; Friedman et al., ; Johnstone et al., ; Mueller et al., ). Larger FRNs in adolescents compared to adults may simply indicate that all stimuli, and therefore all external feedback, are relatively more salient for younger participants.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are worrisome because abnormalities in arousal and attention are related to the development of clinical ADHD (Aleksandrov et al 2005;Huang-Pollock et al 2006;Koschack et al 2003). Children with ADHD have numerous co-existing morbidities, including oppositional/defiant disorder in up to 75% (Barkley 1998;Connor et al 2003), substance abuse (Fischer et al 2003), antisocial behavior (Rasmussen and Gillberg 2000), cognitive, and academic problems because of their inability to "stay on task" (Fischer et al 2003;Rasmussen and Gillberg 2000).…”
Section: Adhdmentioning
confidence: 81%
“…Specific cognitive abilities are associated with unique EEG patterns in both the non-engaged (resting) and engaged states of different cognitive activities (Goel & Dolan, 2004;Gray, Chabris & Braver, 2003;Prabhakaran, Smith, Desmond, Glover & Gabrieli, 1997;Rivera, Reiss, Eckert & Menon, 2005;Zhang & Poo, 2001). Using quantitative EEG (QEEG) measures along with evoked potentials (EP and ERP) measures, cognitive processes can be quantified and a more specific determination made as to which brain functions appear to be inhibiting an individual's performance (Zani & Proverbio, 2003;Atherton, Zhuang, Bart, Hu, & He, 2003;Aleksandrov, Polyakova, & Stankevich, 2003;Ferstl & von Cramon, 2001;Newman, Carpenter, Varma, & Just, 2003;Geake & Hansen, 2005). When reviewing the biomedical literature it has also been found that some of the underlying cognitive performance problems may be related to underlying health issues which disturb cognitive processes.…”
Section: Introductionmentioning
confidence: 99%